2013
DOI: 10.5830/cvja-2013-041
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation during cardiopulmonary bypass did not attenuate inflammatory response or affect postoperative outcomes : cardiovascular topic

Abstract: IntroductionCardiopulmonary bypass causes a series of inflammatory events that have adverse effects on the outcome. The release of cytokines, including interleukins, plays a key role in the pathophysiology of the process. Simultaneously, cessation of ventilation and pulmonary blood flow contribute to ischaemia–reperfusion injury in the lungs when reperfusion is maintained. Collapse of the lungs during cardiopulmonary bypass leads to postoperative atelectasis, which correlates with the amount of intrapulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…Under strong pathological stimuli, cytokines are produced and cascade reactions are triggered. Reperfusion injury following cardiac arrest is closely associated with pro-inflammatory cytokines, including TNF-α, IL-1 and IL-6 (21). The current study demonstrated that treatment with quercetin significantly inhibited the activation of IL-6 and TNF-α release and suppressed ROS generation in CPR model rats.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Under strong pathological stimuli, cytokines are produced and cascade reactions are triggered. Reperfusion injury following cardiac arrest is closely associated with pro-inflammatory cytokines, including TNF-α, IL-1 and IL-6 (21). The current study demonstrated that treatment with quercetin significantly inhibited the activation of IL-6 and TNF-α release and suppressed ROS generation in CPR model rats.…”
Section: Discussionsupporting
confidence: 55%
“…Effective and timely CPR may restore the heart beat for the majority of patients (20). However, cerebral injury following resuscitation remains difficult issue for complete rehabilitation (21). Following successful CPR, the autonomic circulation recovery of the cerebral blood flow causes cerebral-reperfusion injury and may cause further aggravation of the prognosis of cerebral functions and mortality (22).…”
Section: Discussionmentioning
confidence: 99%
“…The postbypass extravascular lung fluid was significantly smaller in the VB group compared to the NVB group and extubation time was significantly shorter, hence this study has shown the benefits of maintaining ventilation during CPB on post‐CPB oxygenation and included shorter mechanical ventilation . In contrast, a small study of fifty‐nine patients prospectively randomized to continuous ventilation and no ventilation, during CABG on CPB, showed there was no statistically significant difference in most of the inflammatory makers (IL‐6, IL8, IL‐10, and lactate) . A recent meta‐analysis for patients undergoing cardiac surgery and received ventilation during CPB included seventeen trials with 1162 patients, showed that ventilation during CPB significantly increased post‐CPB PaO 2 /FiO 2 ratio, but there was no sufficient evidence to show that ventilation during CPB could influence long‐term prognosis of these patients …”
Section: Discussionmentioning
confidence: 72%
“…18,19 Ultimately, 15 articles published between 1993 and 2016 involving 748 patients were selected for this systematic review. 10,11,13,18,[20][21][22][23][24][25][26][27][28][29][30][31] All these studies compared ventilation with or without PEEP, apnea with CPAP, and apnea without CPAP (control) as their primary research purpose.…”
Section: Resultsmentioning
confidence: 99%
“…9 Continuous ventilation with a low tidal volume during CPB appears to reduce extravascular lung water and certain proinflammatory and anti-inflammatory mediator levels. [10][11][12][13][14][15] Whether ventilation during CPB improves a patient's clinical outcomes and oxygenation status remains unclear.…”
mentioning
confidence: 99%